Women Who Sell Sex A Review of Psychological Research With Clinical Implications - Krumrei Mancuso, Elizabeth; Postlethwaite, Bennett E. (Springer International Publishing : Imprint: Springer, 2020)
XI, 181 p. 1 illus.